Are Investments in Groundwater Irrigation Profitable? A Case of Rice Farms from South India1. (8th October 2012) - Varghese, Shalet Korattukudy; Buysse, Jeroen; Frija, Aymen; Speelman, Stijn; Van Huylenbroeck, Guido
<x xml:space="preserve">Abstract</x> Varghese, Shalet Korattukudy, Jeroen Buysse, Aymen Frija, Stijn Speelman, and Guido Van Huylenbroeck, 2012. Are Investments in Groundwater Irrigation Profitable? A Case of Rice Farms from South India. Journal of the American Water Resources Association (JAWRA) 1‐15. DOI: 10.1111/j.1752‐1688.2012.00690.x Abstract: This article examines the profitability of cultivating double rice under bore well irrigation, given the cumulative interference of and reduced life span of wells, and thus increases the cost of groundwater extraction and use. The overexploitation of groundwater is a common stock problem and the cultivation of water intensive crops, such as rice, further exacerbates the overdraft of groundwater. Under these circumstances, we quantify the marginal benefit of irrigation investments in rice farming by estimating the probability of having a double rice crop as a function of the investment made in wells. Using this information, we explore profit maximization behavior of farms with a mathematical programming model to derive individual economic optima of irrigation costs. The results demonstrate that the ongoing overexploitation of groundwater, and its use to cultivate an economically inefficient crop, such as rice, has resulted in low profitability at farm level. A sensitivity analysis found that even when the investment in irrigation wells is reduced by 70%, small farms are still not economically efficient, thereby confirming the Tragedy of the Commons. Raising awareness amongst farmers with regard to the economics of irrigation would facilitate the participatory implementation of control mechanisms to regulate groundwater extraction.